2018
DOI: 10.1108/caer-02-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder preferences and willingness-to-pay measures for microcredit

Abstract: Purpose -The purpose of this paper is to examine smallholders' preferences and willingness to pay for microcredit products with varying attribute combinations, in order to contribute to the debate on the optimal design of rural microcredit. Design/methodology/approach -Data used in this study are based on a discrete choice experiment from 552 randomly selected respondents. Mixed logit and latent class models are estimated to examine the choice probability and sources of preference heterogeneity. Endogenous att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 54 publications
2
23
2
1
Order By: Relevance
“…In addition, more recent studies have revealed that respondents participating in discrete choice experiences often ignore certain attributes in their decision-making process (called ANA). Resulting biases in modelling occur when these aspects are not taken into account [ 28 , 38 , 39 ]. Two approaches were proposed to account for the ANA.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, more recent studies have revealed that respondents participating in discrete choice experiences often ignore certain attributes in their decision-making process (called ANA). Resulting biases in modelling occur when these aspects are not taken into account [ 28 , 38 , 39 ]. Two approaches were proposed to account for the ANA.…”
Section: Methodsmentioning
confidence: 99%
“…Stated ANA is an experimental approach, which consists of asking the respondent to answer specific questions about the attribute ignored during decision-making [ 24 ]. Inferred ANA is an econometric approach that provides a better fit for the model, while the stated ANA is not consistent[ 27 , 28 ]. First, the fact that respondents attribute low importance to certain attributes, which could be ignored at the beginning of their choices, leads to overestimation [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations